New Data from the RECORD Study - Vinall, Phil (MD Conference Express, 2009)
This article discusses two analyses from the Rosiglitazone Evaluated for Cardiac Outcomes and Regulation of Glycemia in Diabetes study [RECORD; NCT00379769; Home PD et al. Lancet 2009] of cardiovascular outcomes in patients who were treated with rosiglitazone.